Effects of HfB2 addition on the oxidation resistance, microstructure, and mechanical properties of pressureless sintered ZrB2-SiC composite - Mashhadi M.; Salimi I.G.; Golieskardi M. (Begell House Inc., 2023)
Microstructure; Molybdenum compounds; Oxidation resistance; Particle size; Silicon carbide; Vickers hardness; X ray diffraction analysis; Zirconium compounds; Nano-sized particles; Oxidized surfaces; Oxygen penetration; Pressureless-sintered; Reinforcing phase; SiC-based ceramics; Silicon carbides (SiC); Solid solution formation; Hafnium compounds